Self-Esteem in the Organization of Interpersolnal Interaction Among Youth qnd Adolescence Age People - Maryna Klymenko; Viktor Plokhikh (Вісник Харківського національного університету імені В.Н. Каразіна. Серія: Психологія)
The issue of organizing interpersonal interaction in relation to the formation of self-esteem in youth and adolescence age people, especially those making life-defining decisions under the burdening conditions of a military conflict, is highly relevant. The aim of the study is to identify the characteristics of self-esteem in accordance with different types of interpersonal attachment in young adults. The sample consisted of 68 young adults. The following methods were used to obtain empirical data: S. Budassi’s method (for determining self-esteem), E. Chen’s method (for determining the type of interpersonal attachment), and H. Eysenck’s method (for identifying maladaptive psychological states). Results: No direct linear statistical relationships were found between the self-esteem and interpersonal attachment of the subjects. The relationship between self-esteem and attachment was determined using cluster analysis in two variants: by the parameter "self-esteem" and simultaneously by the parameters "secure attachment" and "insecure attachment." In both variants, with some differences, one group with high adequate self-esteem, low insecurity of attachment, and elevated secure attachment values was identified, and another group with opposite results was found. The groups significantly differed in terms of self-esteem (U = .00, p < .001 and U = 386.50, p = .036), insecure attachment (U = 297.00, p = .009 and U = 15.00, p < .001), and in one variant by secure attachment (U = 409.50, p = .261 and U = 266.50, p < .001). It was found that individuals in the group with high adequate self-esteem, compared to others, had lower expressions of maladaptive psychological states: anxiety (U = 345.00, p = .048 and U = 262.00, p < .001), frustration (U = 327.00, p = .027 and U = 295.50, p = .001), aggression (U = 365.00, p = .086 and U = 356.00, p = .013), and rigidity (U = 145.50, p < .001 and U = 269.50, p < .001). Conclusions: It has been established that high adequate self-esteem corresponds to a pronounced ability of the individual to organize constructive interaction with a secure type of interpersonal attachment and a low level of vulnerability to the destructive influences of the current situation. Lower self-esteem of the subjects is associated with increased vulnerability to destructive influences and insecure interpersonal attachment. Maladaptive psychological states in young adults are linked to lower self-esteem and increased insecurity of interpersonal attachment.